On the fauna of false scorpions (Arachnida: Pseudoscorpiones) of south-eastern Belarus - Artiom M. Ostrovsky (Cherepovets State University, 2020)
Seven species of the false scorpions have been found in the south-eastern Belarus during targeted studies in 2017–2019. Sylvatic forms represent a significant part of species diversity of the regional fauna of the false scorpions. Only one species, Chelifer cancroides (Linnaeus, 1761), occurs in synanthropic habitats.